2011
DOI: 10.1248/bpb.34.856
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perfluorinated Fatty Acids with Different Carbon Chain Length on Fatty Acid Profiles of Hepatic Lipids in Mice

Abstract: A growing body of evidence supporting the key role of fatty acid species in maintaining systemic metabolic homeostasis has been accumulated in recent years. Many studies showed that free fatty acids and a particular molecular species of phosphatidylcholine (PC), palmitoyl-oleoyl-PC, extend molecular effects to cellular homeostasis as lipid signaling molecules through nuclear receptors.1-3) Palmitic acid (16 : 0) and stearic acid (18 : 0) are known to cause endoplasmic reticulum stress, leading to inductions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…Furthermore, in accordance with this suggestion, Kudo et al [21] observed in mice treated with perfluorinated fatty acids, zenobiotics used as surfactants in various industrial products, that oleic acid was inversely related to arachidonic acid in hepatic phospholipids and total lipids.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, in accordance with this suggestion, Kudo et al [21] observed in mice treated with perfluorinated fatty acids, zenobiotics used as surfactants in various industrial products, that oleic acid was inversely related to arachidonic acid in hepatic phospholipids and total lipids.…”
Section: Discussionmentioning
confidence: 57%
“…The finding of a negative correlation between OA and AA also in mice treated with perfluorinated fatty acids [25], zenobiotics used as surfactants in various industrial products, would seem in support of the contention that the inverse relationship between this couple of fatty acids exists in many species.…”
Section: Discussionmentioning
confidence: 87%
“…Research has proven that FAs of different lengths have unique chemical properties (Layden et al, 2013). In fact, perfluorinated FAs (PFFAs), which are FA analogs (Kudo et al, 2011), were shown to inhibit GJCs in a concentration-dependent manner in a liver epithelial cell line due to their aliphatic chains ranging from 7 to 10 carbons. PFFAs, on the other hand, with 2–5 or 16–18 carbon chain lengths had no effect on GJCs (Upham et al, 1998, 2009).…”
Section: Regulation Of Gap Junction Channels By Fatty Acidsmentioning
confidence: 99%
“…It is thus possible that PFFAs activate membrane receptors, which in turn activate signaling proteins such as protein kinases (Upham et al, 2009). It should also be considered that PFFAs with a carbon chain between 6 and 9 carbons increase the liver FA profile after 5 days of treatment, with specific increases in palmitoleic acid (PO, 16:1), OA (18:1) and eicosatrienoic acid (20:3) content (Kudo et al, 2011). Consequently, treatment under different exposure times may also induce different effects (e.g., acute vs. chronic treatments).…”
Section: Regulation Of Gap Junction Channels By Fatty Acidsmentioning
confidence: 99%